Supercapacitors aging assessment in wind/tidal intermittent energies application with variable temperature. (February 2022) - Sarr, Cheikh Tidiane; Camara, Mamadou Baïlo; Dakyo, Brayima
Highlights: Supercapacitors degradation using current ripple rate temperature and cycles number. Supercapacitors aging modeling using current ripple rate, temperature, cycle's number. Micro-grid power fluctuation mitigation using supercapacitor aging model. Abstract: This paper presents the supercapacitors characterization and modeling considering the influence of the intermittent current's ripple rate, the temperature and cycling factor. The aim of the study is to propose supercapacitors aging model that can be used in adaptive energy management based on the micro-grid power fluctuations mitigation in variable temperature conditions. The model of the supercapacitors is dedicated to multi-source systems such as distributed power generation systems based renewable energies (wind, tidal and/or photovoltaic). Energetic performances of the supercapacitors used in these systems can be altered by the critic temperatures and intermittency of the supercapacitors current allocated to the micro-grid power fluctuations mitigation due to renewable energies. Paper contribution is focused on the supercapacitors parameters degradation study according to the combination of the intermittent current's ripple rate, the temperature and the number of the cycles. Experimental tests are performed through charge/discharge operations using intermittent current waveforms with several temperature conditions. Experimental data are like to simulations outcomes with a good concordance. Therefore, the proposed model is adequate to describe the degradation of the supercapacitor's parameters due to intermittent current and using temperature.